2016
DOI: 10.1097/pas.0000000000000678
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Cell Melanoma and Interdigitating Dendritic Cell Sarcoma

Abstract: Intranodal spindle cell lesions on biopsy are problematic for a surgical pathologist, often requiring an extensive immunohistochemical evaluation with variable and frequently unsatisfactory results. In the absence of a history of malignancy, the differential diagnosis of a spindle cell tumor must include both a primary nodal proliferation and a metastatic process. Particularly challenging are those lesions that share morphologic and immunohistochemical features; spindle cell melanomas (SCM) and interdigitating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…SOX‐10 is a reliable marker in evaluating sentinel lymph nodes for metastatic melanoma and identifying rare tumor cells in heavily regressed areas of metastatic melanoma with abundant melanophages . Immunohistochemical evaluation with SOX‐10 also has found utility in evaluation of intranodal spindle cell tumors …”
Section: Discussionmentioning
confidence: 99%
“…SOX‐10 is a reliable marker in evaluating sentinel lymph nodes for metastatic melanoma and identifying rare tumor cells in heavily regressed areas of metastatic melanoma with abundant melanophages . Immunohistochemical evaluation with SOX‐10 also has found utility in evaluation of intranodal spindle cell tumors …”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry is a helpful tool in distinguishing SCM from other sarcomas and carcinomas ( 9 , 10 ). However, diagnosis remains a challenge as a number of sarcomas share some morphological and immunohistochemical features with SCM ( 5 , 11 ). Differentiation of SCM from desmoplastic melanoma is difficult because both melanomas are characterized by atypical, spindled, malignant melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of case reports and incomplete retrospective case studies of the differential diagnostic viewpoints of SCM exist ( 3 , 4 , 11 15 ). To the best of our knowledge, few studies have reported SCM incidence, clinicopathologic features, treatment, treatment outcome and disease-specific independent prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the MAPK pathway, as reported in case reports, were identified in a subset of tumors herein [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Our findings also highlight the diagnostic challenge of IDCS and its distinction from spindle‐cell melanoma, given their histologic and immunophenotypic overlap [ 55 ]. In difficult cases, analysis of mutation signature by NGS may be helpful in distinguishing metastatic melanoma from IDCS.…”
Section: Discussionmentioning
confidence: 74%